A solitary angiokeratoma on the toe of a teenaged girl. Issue 4 (9th June 2022) - Hatfield, Jess; Preston, Allie K.; Hendrick, Sophia J.
Abstract: An angiokeratoma is a benign vascular lesion that appears as one or more red to black papules with a verrucous surface. Histologically, it is defined by ectatic, thin-walled vessels in the papillary dermis, acanthosis with elongated rete ridges, and compact hyperkeratosis. Solitary angiokeratoma is one of five defined subtypes of angiokeratoma. We report the case of an 18-year-old woman with a "wart" that had been present for many years. After treatment with several over-the-counter wart therapies, several rounds of paring plus cryotherapy, and Candida antigen injections failed, a shave biopsy was taken to remove the lesion, and histopathologic examination was consistent with an angiokeratoma. This case demonstrates the importance of considering angiokeratoma in the differential diagnosis of a wart, particularly one recalcitrant to treatment.